Archaeology and Ancient Israelite Religion - Faust, Avraham (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Israelite religions have always fascinated scholars. Initial studies used the Bible as their main source of information and attempted to read it critically in order to learn about the religion of ancient Israel. With the advent of modern research in the Near East, more and more information on other Ancient Near Eastern religions was accumulated and initially used to illuminate Israelite religious practices as described in the Bible, but gradually led to challenging some of the accepted truisms. The new information was collected mainly through archaeological excavations, and archaeology had gradually become a major player in the study of ancient Israelite religion(s) and religious practices. The massive amount of information on the various subthemes related to Israelite religions, the shifting trends in scholarship, the multiplicity of approaches, and the interdisciplinary nature of the field means that no single scholar can master all the data today. Indeed, there is currently no comprehensive and updated book that covers all or even most aspects pertaining to Israelite religion(s). This volume is a partial attempt to fill some of this lacuna. The volume includes a number of broad, summarizing studies, presenting readers with the up-to-date state of the research on a number of important issues, from Solomon's temple to broader studies of the loci of cultic activity in ancient Israel through to analysis of the difference between the "official" and "popular" expression of religion, the place of women in Israelite cult(s), similarities and differences between the religious practices in Israel and Judah and those of other Iron Age religions, and the religion of some of Israel's neighbors to the role of zooarchaeology in the study of religion, ancient Israelite festivals, and more.